Assessing Potential Groundwater Storage Capacity for Sustainable Groundwater Management in the Transitioning Post‐Subsidence Metropolitan Area - Shao‐Hung Lin; Jyr‐Ching Hu; Shih‐Jung Wang (Water Resources Research)
Abstract Many major cities worldwide have inevitably experienced excessive groundwater pumping due to growing demands for freshwater in urban development. To mitigate land subsidence problems during urbanization, various regulations have been adopted to control groundwater usage. This study examines the transition in the post‐subsidence stage, especially in metropolitan areas, to adaptively adjust subsidence prevention strategies for effective groundwater management. Taking the Taipei Basin as an example, historical data reveals significant subsidence of more than 2 m during early urban development, with subsidence hazards largely mitigated over decades. However, the rising groundwater level poses a risk to the stability of engineering excavations. In this study, 29 X‐band Cosmo‐Skymed constellation (CSK) images were utilized with the Persistent Scatterer InSAR (PSInSAR/PSI) technique to monitor surface displacements during the construction of the Mass Rapid Transit system. Correlating groundwater levels helps identify the heterogeneous hydrogeological environment, and the potential groundwater capacity is assessed. PSI time‐series reveal that approximately 2 cm of recoverable land displacements correspond to groundwater fluctuations in the confined aquifer, indicative of the typically elastic behavior of the resilient aquifer system. The estimated groundwater storage variation is about 1.6 million cubic meters, suggesting this potential groundwater capacity could provide available water resources with proper management. Additionally, engineering excavation safety can be ensured with lowered groundwater levels. This study emphasizes the need to balance groundwater resource use with urban development by adjusting subsidence prevention and control strategies to achieve sustainable water management in the post‐subsidence stage.